Hubungan Kepuasan Keluarga Pasien pada Pelayanan Pendaftaran Rawat Inap dengan Mutu Pelayanan Di Rumah Sakit Daerah Idaman Banjarbaru - Nirma Yunita; Rina Gunarti (HB PRESS, 2022)
An accurate level of patient satisfaction is needed to improve service quality. Measuring the level of patient satisfaction needs to be done regularly, regularly, accurately, and continuously. Family satisfaction is very dependent on the perceptions and expectations of families as recipients of nursing care, so as service providers in this case health workers need to know the factors that influence family satisfaction. High performance and quality of service are the most important factors in achieving patient satisfaction. Community satisfaction in 2021 at the Idaman Banjarbaru Regional Hospital was obtained from July to September or made quarterly that the average community satisfaction in inpatient registration is 75% stating that they are satisfied with the services of inpatient registration officers. This study was conducted at the Inpatient Registration Place at Idaman Hospital, Banjarbaru. The results showed that six patients’ families (60%) were not satisfied with the service due to long waiting times and four patients’ families were satisfied with the service. So that dissatisfaction was obtained which results in the quality of service at the Idaman Regional Hospital not being good. This research used analytical method. The results and conclusions of this study were the patient's family satisfaction obtained 30 respondents (75%) satisfied and 10 respondents (25%) dissatisfied. The quality of service obtained by 33 respondents (82.5%) was good and 7 respondents (12.5%) was not good. The relationship between patient family satisfaction in inpatient registration services at the Idaman Regional Hospital Banjarbaru obtained the r value of the relationship between patient family satisfaction and service quality of 0.010. Thus, the correlation between the two variables was significant. It was proven that patient’s family satisfaction was associated with the service quality at the Idaman Regional Hospital Banjarbaru.